Elongated VCE blast waves and structural response. Issue 2 (20th November 2017) - Geng, Jihui; Mander, Thomas; Thomas, J. Kelly; Baker, Quentin
Abstract : Elongated congested volumes are common at chemical processing and petroleum refining facilities due to the arrangement of processing units, but there have been relatively few evaluations reported for the blast loads produced by elongated vapor cloud explosions (VCEs). The accidental VCE that occurred at the Buncefield, UK facility in 2005 involved an elongated congested volume formed by the trees and undergrowth along a portion of the site boundary. Some of near‐field damage indicators present at the Buncefield site could not be reasonably explained using existing standard VCE blast load prediction techniques that are based on an assumption that the congested volume filled with flammable gas cloud is hemispherical and located at grade level. This paper summarizes recent work to define the characteristics associated with elongated congested volume VCEs and identify differences relative to standard VCEs involving compact congested volume geometries. The main conclusions from this work with regard to the blast wave shape for an elongated congested volume deflagration are: (1) the blast wave behaves as an acoustic wave along the long axis, (2) the blast wave has a very quick transition from the positive phase peak pressure to the negative phase peak pressure (i.e., quick relative to the positive phase duration), and (3) the magnitude of the pressure drop between the peak positive and negative pressures diminishes quickly with distance outside the congested volume. These observations are not consistent with the behavior of a compact congested volume geometry VCE blast wave. Deflagration and deflagration‐to‐detonation transition (DDT) regimes were also identified for unconfined elongated congested volume VCEs as a function of the normalized flame travel distance and flame speed. These regimes were verified with existing test data, including data from the on‐going RPSEA test program. These observations and the DDT regime identification provide a frame of reference to develop a better understanding of elongated congested volume VCEs. Generic structures, with properties typical of conventional construction, were analyzed to illustrate the effect of the elongated congested volume VCE blast loads on structural response. The results show that, for an elongated congested volume VCE, a high flame speed deflagration may result in more severe structural response in the near‐field than for a detonation (i.e., due to a DDT). These results provide an alternative near‐field damage indicator analysis approach for the investigation of elongated congested volume VCE incidents. © 2017 American Institute of Chemical Engineers Process Saf Prog 37: 283–293, 2018